2012
DOI: 10.4049/jimmunol.1102984
|View full text |Cite
|
Sign up to set email alerts
|

Human MSH6 Deficiency Is Associated with Impaired Antibody Maturation

Abstract: Ig class-switch recombination (Ig-CSR) deficiencies are rare primary immunodeficiencies characterized by defective switched isotype (IgG/IgA/IgE) production. Depending on the molecular defect, defective Ig-CSR may also be associated with impaired somatic hypermutation (SHM) of the Ig V regions. Although the mechanisms underlying Ig-CSR and SHM in humans have been revealed (at least in part) by studying natural mutants, the role of mismatch repair in this process has not been fully elucidated. We studied in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 47 publications
1
42
1
1
Order By: Relevance
“…An analysis of three patients with biallelic PMS2 and eight with biallelic MSH6 mutations has shown that constitutional deficiency of these MMR genes leads to impaired immunoglobulin (Ig) class switch recombination characterised by a decrease or absence of IgG2, IgG4 and IgA concomitant (particularly in young patients) with increased IgM levels, that is, hyper-IgM syndrome 36 37. IgA deficiency indicative of this humoral defect was also observed in a patient with a homozygous MSH2 mutation 38.…”
Section: The Clinical Phenotype Of Cmmrd As Deduced From the Known Casesmentioning
confidence: 99%
“…An analysis of three patients with biallelic PMS2 and eight with biallelic MSH6 mutations has shown that constitutional deficiency of these MMR genes leads to impaired immunoglobulin (Ig) class switch recombination characterised by a decrease or absence of IgG2, IgG4 and IgA concomitant (particularly in young patients) with increased IgM levels, that is, hyper-IgM syndrome 36 37. IgA deficiency indicative of this humoral defect was also observed in a patient with a homozygous MSH2 mutation 38.…”
Section: The Clinical Phenotype Of Cmmrd As Deduced From the Known Casesmentioning
confidence: 99%
“…The MutSα-deficient mice exhibit an altered mutation spectrum, with a 75-90% decrease in mutations at A:T bp [44, 45, 48]. A marked decline in A:T mutagenesis has also been observed in MSH6-deficient humans [49]. Exo1 −/− mice have decreased SHM and mutations at A:T bp [50, 51].…”
Section: Mutsα Complex Generates A:t Mutations During Shmmentioning
confidence: 99%
“…Furthermore, defects in immunoglobulin class switch recombination (indicated by decreased levels or absence of IgG2, IgG4 and IgA together with increased IgM levels) are also associated with CMMR-D syndrome. 10,11 At least one CMMR-D patient initially presented with a primary immunodeficiency. 11 Despite publication of 4100 CMMR-D patients, diagnosis may still be delayed in many childhood cancer patients.…”
Section: Introductionmentioning
confidence: 99%